New records of aturid water mites from Australia (Acari: Hydrachnidia; Aturidae), with the description of fifteen new species - Smit, Harry (Zootaxa, 2018)
The following fifteen new species are described of the water mite family Aturidae from Australia: Austraturus cavatus n. sp., A. denticulatus n. sp., A. dilatipalpis n. sp., A. extendens n. sp., A. sagittalis n. sp., A. triprojectus n. sp., A. villosus n. sp. and Axonopsella bipartita n. sp., A. carnarvon n. sp., A. curtiseta n. sp., A. elongata n. sp., A. kakadu n. sp., A. magniseta n. sp., A. purpurea n. sp. and A. rosea n. sp.. New records are given for Queensland, South Australia, Tasmania, Victoria, New South Wales, Northern Territory and Western Australia. New distributional records are provided for many species.